2019
DOI: 10.3342/kjorl-hns.2019.00535
|View full text |Cite
|
Sign up to set email alerts
|

A Nasal Myoepithelioma Removed through Preoperative Embolization and Endoscopic Surgery: A Case Report and Literature Review

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (https://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…5) In Korea, so far, a myoepithelioma in the sinonasal cavity has been reported only in the nasal septum and nasal cavity, and no cases in the maxillary sinus have been reported yet. 4,6,7) In this case, a myoepithelioma of maxillary sinus origin was reported for the first time in Korea.…”
Section: A B Cmentioning
confidence: 74%
See 2 more Smart Citations
“…5) In Korea, so far, a myoepithelioma in the sinonasal cavity has been reported only in the nasal septum and nasal cavity, and no cases in the maxillary sinus have been reported yet. 4,6,7) In this case, a myoepithelioma of maxillary sinus origin was reported for the first time in Korea.…”
Section: A B Cmentioning
confidence: 74%
“…3) The salivary glands are the most com-mon site of myoepithelioma, but it can also occur in other sites such as the external auditory canal, orbit, and nasal cavity. 4) Given that diagnosis is difficult even for pathologists because of diverse histomorphological and immunohistochemical characteristics, it is important to keep in mind the possibility of myoepithelioma. The occurrence of myoepithelioma in the sinonasal cavity is rare, and only 15 cases have been reported thus far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of English-language literature, published in 2019, revealed only 12 previous cases of sinonasal myoepithelioma, 12 and there have been no subsequent publications of case reports in the literature since this review. Patients present with chronic nasal obstruction without secondary symptoms and with a painless mass on examination.…”
Section: Discussionmentioning
confidence: 93%